Relationship between Dark Triad, Mental Health, and Subjective Well-being Moderated by Mindfulness: A Study on Atheists and Muslim Students - Aamer Aldbyani; Mohammed Hasan Ali Al-Abyadh (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
Research indicates that mindfulness is related to mental health (anxiety, depression, and general health) and well-being. However, its impact on individuals who have the Dark Triad (DT) personality remains unclear. We examined the relationship between the DT constructs (narcissism, psychopathy, and Machiavellianism), mental health, and subjective well-being with mindfulness as the moderator variable. A total of 764 (Atheist=412; Muslims=352) university students were recruited to complete the Dark Triad personality scale (DM), Mindful Attention Awareness Scale (MAAS), Beck Depression Inventory-II (BDI-II), Trait Anxiety scale (STAI), General Health Questionnaire (GHQ), and Subjective Well-Being scale (SWB). Pearson's correlations and PROCESS macro were used to evaluate associations between these variables and whether mindfulness moderated the associations between DT constructs, mental health, and subjective well-being. The results revealed that DT statistically significant predictor of mental health but only in low mindfulness levels. While two DT constructs, narcissism and Machiavellianism, significantly predict subjective well-being only for participants with high mindfulness levels.